Integrated crop-livestock versus conventional systems: Effects on the chemical and physical characteristics of an Oxisol - Augusto, Jeferson Garcia; de Paz, Claudia Cristina Paro; Mendonça, Gabriela Geraldi; Moitinho, Mara Regina [UNESP]; Menegatto, Leonardo Sartori; Bolonhezi, Denizart; Salles, Márcia Saladini Vieira; Simili, Flávia Fernanda (Wiley, 2024)
Studies have reported improvements in soil quality in integrated crop-livestock systems (ICLS) when compared to conventional systems. The hypothesis of this study was that ICLS improve Oxisol quality due to the use of intercropping, adding pasture and cattle to the systems. The aim of the study was to evaluate the chemical and physical characteristics of an Oxisol and pasture production in the integrated system versus conventional system. We compared two conventional systems: crop system (maize grain production) and livestock system (beef cattle on single pasture) and, four ICLS: maize plus Marandu palisade grass sown simultaneously without herbicide (ICLS-1); maize plus Marandu palisade grass sown simultaneously with herbicide (ICLS-2); maize plus Marandu palisade grass in lagged sowing (ICLS-3); and maize plus Marandu palisade grass sown simultaneously in maize rows and inter-rows with herbicide (ICLS-4). A randomized block design with six treatments and three replicates was used. The results suggest improvements in soil quality, including soil organic carbon (ICLS-4), total nitrogen, and nitrogen stocks (ICLS-1, ICLS-2, and ICLS-4). The intercropping technique influenced pasture production and soil quality during the implementation of integrated systems. The lowest soil strength was obtained for the crop system compared to systems with grazing animals but there were no changes in the soil physical characteristics that could compromise the production system.
Keywords: Brachiaria brizantha; Marandu; soil organic carbon; soil strength; soil total nitrogen; Zea mays L